2020
DOI: 10.7759/cureus.10065
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Ketoacidosis in an Euglycemic Patient

Abstract: Diabetes is a common disease, and the number of patients is increasing every year. We report a case of a 34-year-old man with a history of diabetes mellitus (diagnosed at eight years old) and was on treatment with tablet glimepride with poor compliance. The patient sought consultation due to vomiting and abdominal pain 12 hours after onset along with burning micturition for four days. His initial blood sugar random (BSR) level was 84 mg/dL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In our case, the blood glucose was 218 mg/dL. Mumtaz H et al [ 10 ], in his case report of euglycemic DKA, reported that blood glucose in their case was only 84 mg/dL. In a retrospective case series by Menghoum N et al [ 12 ], the glycemia ranged from 112 to 280 mg/dL.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In our case, the blood glucose was 218 mg/dL. Mumtaz H et al [ 10 ], in his case report of euglycemic DKA, reported that blood glucose in their case was only 84 mg/dL. In a retrospective case series by Menghoum N et al [ 12 ], the glycemia ranged from 112 to 280 mg/dL.…”
Section: Discussionmentioning
confidence: 50%
“…Each of them describes different precipitating factors compared to ours. These include pregnancy [ 9 ], urinary tract infection [ 10 ], surgery [ 11 ], dehydration and prolonged fasting [ 12 ]. In our scenario, acute stroke was the possible etiology, after which the patient was diagnosed with euglycemic DKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGLT2 inhibitors promote glucosuria leading to decreased plasma glucose level, which promotes glucagon production and discourages insulin release thereby inducing DKA with low blood glucose [1]. Reported median glucose levels range between 211 and 328 mg/dL [2,3]. DKA tends to have precipitating factors that cause stress in the body, such as preoperative and postoperative settings, sepsis, dehydration, and starvation [3][4][5].…”
Section: Discussionmentioning
confidence: 99%